PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV DI UPTD SD NEGERI LABUHAN RATU TIGA: Penelitian Tindikan Kelas - Lusi Ratnasari; Bambang Ariyanto; Sulis Anjarwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low IPAS learning outcomes of fourth-grade students at UPTD SD Negeri Labuhan Ratu Tiga, caused by the lack of variation in learning methods and the suboptimal level of active student involvement. This study aims to improve learning outcomes in the IPAS topic "Cerita tentang Daerahku" through the STAD-type cooperative learning model for fourth-grade students at UPTD SD Negeri Labuhan Ratu Tiga. The method used was Classroom Action Research (CAR) consisting of two cycles. The subjects were 26 students, with data collection techniques involving learning outcome tests and observations. The results showed a significant improvement in learning outcomes. In Cycle I, student mastery reached 17 students (65%), which increased to 22 students (85%) in Cycle II, representing a 20% improvement. The conclusion of this study is that the implementation of the STAD model is effective in improving the IPAS learning outcomes of fourth-grade students at UPTD SD Negeri Labuhan Ratu Tiga. Teachers are suggested to implement this model as a learning innovation to enhance student collaboration.